KONDISI LAMUN DI PERAIRAN DUSUN ORY PULAU HARUKU KABUPATEN MALUKU TENGAH - Roos Nilawati Marasabessy; Wilda Fesanrey; Amaliah F. Ambon; Susiati Susiati (Fakultas Perikanan dan Kelautan Universitas Riau, 2022)
Research on the condition of seagrass communities in the waters of Ory village is important to do as a basis for management strategies and data on seagrass meadow conditions. The purpose of this study is to find out the current seagrass conditions (2021) and to find out the structure of the seagrass meadow community formed and the biota associated with seagrass in Ory waters. This research was conducted in June-August 2021 in the waters of Ory village of Haruku Island, Central Maluku District. The sampling technique in this study is based on the use of the square transect line method. Seagrass sampling is done at low tide using a square of 0.5 x 0.5 m with the size of each plot of 0.1 x 0.1 m as much as 25 plots. The data analysis method for occurence frequency calculation, type coverage, while to know seagrass conditions. Based on the results of the study, there are 5 types of seagrass in the waters of Ory village, namely Thalassia hemprichii, Enhalus acoroides, Cymodocea rotundata, Halophila ovalis, and Halodule pinifolia. The density value of seagrass in the waters of Ory village is 322 shoots / m2 (very tight), the frequency of Enhalus acoroides species is more widespread than other types, and the covering value of seagrass is 98.45% (good, healthy / rich). The highest INP is in the Enhalus acoroides, and the biota species associated with seagrass are A. granosa, Linckia laevigata, P. nododsus, and Holothuria scabra